2013
DOI: 10.1111/all.12195
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of penicillin allergy revisited: the value of case history, skin testing, specific IgE and prolonged challenge

Abstract: The data suggest that case history is often insufficient to discriminate between immediate reactors and nonimmediate reactors. A 7-day challenge with the culprit β-lactam may yield more positive reactions than the accepted one- or 2-day challenge. Interpretation of skin testing should be made with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 34 publications
(50 reference statements)
9
100
2
1
Order By: Relevance
“…This finding is consistent with the study of Hjortlund et al [32] who reported that 6 patients categorized as NIR based on histories, reacted immediately during challenge testing. Hence, the case history is not generally sufficient to discriminate between IRs and NIRs [33].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the study of Hjortlund et al [32] who reported that 6 patients categorized as NIR based on histories, reacted immediately during challenge testing. Hence, the case history is not generally sufficient to discriminate between IRs and NIRs [33].…”
Section: Discussionsupporting
confidence: 92%
“…Although a 7-day challenge has been shown to yield more positive reactions than shorter challenges [150], in the UK, it is common practice to undertake a 3-to 5-day drug challenge.…”
Section: Skin Tests For Non-immediate Hypersensitivity Reactionsmentioning
confidence: 99%
“…Table S2. Examples of increasing drug doses during provocation, modified from Messaad and colleagues [150]. Table S3.…”
Section: Supporting Informationmentioning
confidence: 99%
“…First, drug allergies differ from respiratory and food allergies in terms of the physiological changes that are induced. For instance, it has been shown that penicillin allergies, which are often delayed reactions, involve an immunoglobulin E-independent mechanism, 17 while respiratory allergies such as asthma occur instantaneously as a result of immunoglobulin Emediated hypersensitivity. 15,33 Second, respiratory and food allergies are typically manifested during routine daily activities, while a drug allergy is less apparent, and 9 /L) of eosinophil counts, the discriminative power was 60% sensitivity and 58% specificity for glioma cases compared with nontumor controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that positive PenSTs were observed at similar frequencies among the 4 subsets of control subjects, and collectively, the incidence of positive results (12.5%) was comparable to what has been observed in the general population (7.3%-10.2%). 17,23 All of these results indicated that the control subjects might be able to represent normal subjects. Although no significant differences were observed in eosinophil counts and PenST results between glioma patients with or without steroid use, steroids may have confounded the results.…”
mentioning
confidence: 86%